Comparative Analysis on Chemical Components and Antioxidant Activity for Four Different Varieties of Yunnan Large-leaf White Tea - Chunhua ZHANG; Xuexing YAN; Tinghong CUI; Yuanyan ZHAO; Zhong TAO; Yuefei WANG; Zhiguo SHAN (Shipin gongye ke-ji)
This study aimed to investigate the variations in primary chemical constituents and antioxidant activities of white tea derived from different large-leaf varieties in Yunnan. Yunkang 10, Changye Baihao, Xueya 100 and Jinggu Dabai were selected as the research objects. The contents of main biochemical components and total antioxidant capacity, DPPH free radical scavenging capacity, hydroxyl radical (·OH) scavenging capacity, superoxide anion radical (O2−·) scavenging capacity were detected. The scavenging capacity was combined with correlation analysis and principal component analysis (PCA) to compare its antioxidant activity. The results showed that there were significant differences in the main chemical components of the four Yunnan large-leaf white teas, and the water extract (49.40%), tea polyphenol (35.87%) and phenol-annonia ration (13.36) in Jinggu white tea were significantly higher than those of the other three (P<0.01). Compared with the other three kinds of white tea, Jinggu white tea had the strongest hydroxyl radical (·OH) scavenging rate, DPPH free radical scavenging rate and superoxide anion radical (O2−·) scavenging rate. The results of correlation analysis showed that there was no significant correlation between sensory scores and tea polyphenols, amino acids, phenol-ammonia ratio, flavonoids, and water extracts (P>0.05), but there was a correlation between the main chemical components, among which tea polyphenols were significantly positively correlated with flavonoids and water extracts (P<0.01), and there was also a certain correlation between the main chemical components and antioxidant activity indexes, and the total antioxidant activity was significantly positively correlated with tea polyphenols, flavonoids and water extracts (P<0.01). The results of PCA showed that the antioxidant capacity and comprehensive quality of active components of Jinggu white tea were higher than those of the other three white tea samples. This study preliminarily explored the differences in quality and antioxidant activity of different large-leaved tea varieties, which provided a theoretical basis for the quality regulation of Yunnan large-leaved white tea, and provided data support and scientific basis for the in-depth study of the antioxidant activity of Yunnan large-leaved white tea and the selection of appropriate Yunnan white tea by consumers.